2014
DOI: 10.1177/0193945914524639
|View full text |Cite
|
Sign up to set email alerts
|

Stressors May Compromise Medication Adherence Among Adults With Diabetes and Low Socioeconomic Status

Abstract: Studies examining the impact of stressors on diabetes self-care have been limited by focusing on a single stressor or have been largely qualitative. Therefore, we assessed the stressors experienced by a high-risk population with type 2 diabetes, and tested whether having more stressors was associated with less adherence to multiple self-care behaviors. Participants were recruited from a Federally Qualified Health Center and 192 completed a stressors checklist. Experiencing more stressors was associated with le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…Participants are asked “In the past year (12 months), have any of the following family issues been stressful for you?” with 1=yes and 0=no as response options. Example items include “lack of affordable local transport for my family or myself” and “living in an unsafe neighborhood.” The TAPS score is calculated by summing the “yes” responses across items for a possible range of 0–20 (Osborn et al, 2014). Although the checklist nature of the TAPS precludes examination of internal consistency reliability, the stressors most commonly reported on the TAPS have been similar across samples of patients from FQHCs (Rothberg et al, 2011; Welch et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants are asked “In the past year (12 months), have any of the following family issues been stressful for you?” with 1=yes and 0=no as response options. Example items include “lack of affordable local transport for my family or myself” and “living in an unsafe neighborhood.” The TAPS score is calculated by summing the “yes” responses across items for a possible range of 0–20 (Osborn et al, 2014). Although the checklist nature of the TAPS precludes examination of internal consistency reliability, the stressors most commonly reported on the TAPS have been similar across samples of patients from FQHCs (Rothberg et al, 2011; Welch et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Although the checklist nature of the TAPS precludes examination of internal consistency reliability, the stressors most commonly reported on the TAPS have been similar across samples of patients from FQHCs (Rothberg et al, 2011; Welch et al, 2011). This instrument was developed based on extensive input from healthcare providers and diabetes educators who treat patients at FQHCs (Osborn et al, 2014), enhancing its content and face validity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies, however, have not found associations between stress and adherence (for a review see Morris et al, 2011). Finally, a recent study found that an accumulation of multiple stressors was associated with dietary adherence, but this relationship became non-significant when they controlled for depression (Osborn et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Certain populations have higher rates of non-adherence to diabetes treatment, including racial/ethnic minorities (Osborn, Cavanaugh, et al, 2011), populations with low socioeconomic status (SES; defined as having a limited income, education, or lack of health insurance), and/or persons with more social stressors (Osborn et al, 2014), limited health literacy (Osborn, Cavanaugh, et al, 2011), and depression (Gonzalez et al, 2007; Osborn, Patel, et al, 2011). Factors associated with non-adherence to insulin, specifically, include older age (Egede et al, 2011), being female (Egede et al, 2011; Peyrot et al, 2010), being a racial/ethnic minority (Cramer et al, 2005), having low SES and a T2DM diagnosis (versus type 1 diabetes) (Peyrot et al, 2010), among other factors (Davies et al, 2013).…”
mentioning
confidence: 99%